First in human percutaneous implantation of a balloon expandable transcatheter heart valve in a severely stenosed native mitral valve. Issue 7 (14th March 2014) - Guerrero, Mayra; Greenbaum, Adam; O'Neill, William
<x xml:space="preserve">Abstract</x> Transcatheter implantation of a balloon expandable valve in calcified severely stenosed native mitral valves has recently been described. The two cases reported so far utilized the surgical transapical approach generally used for transapical transcatheter aortic valve replacement. A percutaneous approach has not been published. We report the first successful percutaneous implantation of a balloon expandable transcatheter valve in the native mitral valve without a surgical incision. © 2014 Wiley Periodicals, Inc.